IMPLEMENTASI STRATEGI SEKOLAH MELALUI PEMBELAJARAN PPKN DALAM PENGUATAN KARAKTER PROFIL PELAJAR PANCASILA - Jesica Audina Br Ginting; Sujana, I Putu Windu Mertha; Kertih, I Wayan (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2025)
Abstract Character education is a central focus of the Merdeka Curriculum through the strengthening of the Pancasila Student Profile. The success of character development requires synergy between school strategies and the role of teachers, particularly Civics Education teachers. This study aims to analyse the implementation of school strategies through learning in strengthening the character of the Pancasila Student Profile among students at SMAN 1 Banjar. This research employed a qualitative descriptive approach. The research subjects included the principal, Civics Education teachers, and students. Data were collected through observation, interviews, and documentation, and analysed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results indicate that school strategies are implemented through the integration of Pancasila values into learning activities, reinforcement of school culture, co-curricular and extracurricular programs, and the implementation of the Pancasila Student Profile Strengthening Project (P5). Civics Education teachers act as facilitators, role models, and motivators in internalizing Pancasila values through contextual and participatory learning. However, challenges remain in terms of limited understanding of the Pancasila Student Profile concept and adaptation to the Merdeka Curriculum. Overall, school strategies and the role of Civics Education teachers contribute positively to strengthening students’ character in accordance with the Pancasila Student Profile. Keywords: school strategy, Civics Education teacher, character education, Pancasila Student Profile